Komposisi minyak pati daripada zingiber cassumunar / Rohaiza Saat and Hasnah Mohd Sirat - Saat, Rohaiza; Mohd Sirat, Hasnah (Universiti Teknologi MARA Cawangan Pahang, 2000)
Extraction of the fresh rhizomes of Zingiber cassumunar using hydrodistillation technique gave the essential oil (2.7 g, 0.4 %). The chemical compositions of the essential oil were analysed by a combination of capillary GC and GC-MS. 22 components were identified, which constituted 82.5 % of the oil. Most of the compounds were monoterpenes (60.1 %) with 4-terpineol (20.1 %) as the major constituent. The essential oil also consisted of sesquiterpenes (5.6 %), phenylbutanoid derivatives (15.9 %) and esters (0.9 %).